What encourages care workers to continue working in intellectual disability services in England? Interview findings. (March 2021) - Stevens, Martin; Moriarty, Jo; Manthorpe, Jill; Harris, Jess; Hussein, Shereen; Cornes, Michelle
The article reports research aimed at identifying factors relating to retention in English intellectual disability services, drawing on a study of the social care workforce. The research involved two rounds of interviews with social care managers and staff between 2009 and 2014. The study uses social exchange theory, particularly the idea of 'reciprocity' and the mechanism of 'hope', as a conceptual framework to aid interpretation of the themes relating to retention identified in the interview analysis: 'pay', 'support', 'morale', and 'training' (related to reciprocity) and 'improving quality of life' and 'supporting personal development' (related to hope). Both groups of themes are identified as being particularly appropriate to intellectual disability services. The study concludes that reciprocity and hope seem to interact in factors related to staff retention, although the study suggests that reciprocity rather than hope is directly connected with retention.